1991
DOI: 10.1515/cclm.1991.29.10.657
|View full text |Cite
|
Sign up to set email alerts
|

Dual Effect of Lovastatin and Simvastatin on LDL-Macrophage Interaction

Abstract: Lovastatin and simvastatin which are very potent cellular cholesterol biosynthesis Inhibitors, significantly affect the plasma lipoprotein concentration.After incubation of plasma with 14 C-labelled compounds, radioactivity was found in all lipoprotein fractions but mainly (40%) in high density lipoprotein (HOL), and in the lipoprotein-deficient plasma fraction (20-30%). Dr g-treated lipoproteins showed reduced electrophoretic mobility on cellulose acetate in comparison with control lipoproteins. The lovastati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

1992
1992
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 24 publications
0
4
0
1
Order By: Relevance
“…The relative contribution of this route, compared with direct binding of the drug to the macrophages, in the cellular uptake of pravastatin is not known. Unlike lovastatin and simvastatin [27], incubation of pravastatin with LDL had no effect on the lipoprotein electrophoretic mobility or immunoreactibility with mAb B1B6 (which reacts with the LDL receptor binding domains on the LDL apo B100). Pravastatin, unlike simvastatin, also did not affect LDL composition [27].…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…The relative contribution of this route, compared with direct binding of the drug to the macrophages, in the cellular uptake of pravastatin is not known. Unlike lovastatin and simvastatin [27], incubation of pravastatin with LDL had no effect on the lipoprotein electrophoretic mobility or immunoreactibility with mAb B1B6 (which reacts with the LDL receptor binding domains on the LDL apo B100). Pravastatin, unlike simvastatin, also did not affect LDL composition [27].…”
Section: Discussionmentioning
confidence: 89%
“…Unlike lovastatin and simvastatin [27], incubation of pravastatin with LDL had no effect on the lipoprotein electrophoretic mobility or immunoreactibility with mAb B1B6 (which reacts with the LDL receptor binding domains on the LDL apo B100). Pravastatin, unlike simvastatin, also did not affect LDL composition [27]. LDL may well be an important carrier of statin agents in the circulation [29].…”
Section: Discussionmentioning
confidence: 89%
“…Moreover, a recent report has suggested that clofazimine, one of the drugs that compose the WHO‐MDT regimen for leprosy treatment, exerts its microbicidal activity via the decreasing LD accumulation in infected cells (Degang et al ., ). Interestingly, besides its classical mechanistic action of inhibiting the HMGCR, lovastatin was able to decrease LDL‐Cho uptake in ML‐infected macrophages, corroborating with the literature data (Aviram et al ., ). Of note, lovastatin was shown to more drastically affect ML viability than BCG viability.…”
Section: Discussionmentioning
confidence: 97%
“…endotheliale Monozytenadhäsion [29] und die Cholesterin-Aufnahme und Cholesterin-Anreicherung in Makrophagen reduziert wird [30,31]. Obwohl die Anzahl der LDL-Rezeptoren auf der Makrophagenoberfläche durch Statine erhöht wird, nimmt deren Affinität zum LDL ab [32]. Des weiteren wird die Bildung von Cholesterinestern und konsekutiv deren Aufnahme durch Makrophagen mittels des Enzyms Acyl-CoA: Cholesterin Acyltransferase (ACAT) gestört [33].…”
Section: Pharmakodynamik Der Lipidsenkenden Wirkungunclassified